Understanding emotional and binge eating: from sports training to tailgating - Woolsey, C. L.; Mannion, J.; Williams, R. D.; Steffen, W.; Aruguete, M. S.; Evans, M. W.; Spradley, B. D.; Jacobson, B. H.; Edwards, W. W.; Kensinger, W. S.; Beck, N. C. (The Sport Journal, 2013)
Many athletes are asked to gain weight and even overeat to "bulk up" for their respective sport(s). In addictive behaviors, early exposure and habit formation during the brain`s developing years are highly predictive of continued problems later in life. As with commonly abused drugs, research indicates foods high in sugars and fat also cause large increases in dopamine, serotonin, and, possibly the most important for those who struggle with food dependency, opioids/endorphins. Due to the brain`s hardwired limbic system circuitry and the naturally reinforcing biochemical mechanisms of eating, there are many physical and psychological factors that influence eating behaviors. Psychological eating factors include stress, depression, anxiety, body dissatisfaction, low self-esteem/self-efficacy, and a preoccupation with food, weight, and body shape. Interpersonal factors stem from social interactions and psychosocial variables such as cultural and ecological influences. For drugs of abuse, abstinence only programs are often the only effective method of eliminating dependency; however, these programs are not a possible with eating. Therefore, this review introduces research on mindfulness, which has been shown to be an effective impulse-control strategy for behaviors, such as eating, that are also a basic part of life. Any intervention plan for treating binge and emotional eating should include methods to help increase awareness and emotional resilience. Client-centered positive health behavior change techniques such as Motivational interviewing (MI) also appear to be highly effective in the treatment of emotional and binge eating.